Altered Plasma Clot Properties and Trauma-Related Venous Thromboembolism despite Thromboprophylaxis - Goldman, Sarah; Frączek, Paulina; Szklanny, Krzysztof; Papuga-Szela, Elżbieta; Stanisz, Andrzej; Undas, Anetta (Thrombosis and Haemostasis, 2018)
Background Prothrombotic clot phenotype may characterize patients developing deep vein thrombosis (DVT) despite pharmacological thromboprophylaxis. We studied the role of fibrin clot properties and its potential determinants in individuals who experienced DVT after lower limb injury.Methods In a case–control study, we assessed 50 patients who developed DVT despite prophylactic use of low-molecular-weight heparins (the failed thromboprophylaxis group) after a lower limb injury, and three age- and sex-matched control groups, 50 patients each: (1) patients with trauma-related DVT without prior thromboprophylaxis; (2) individuals with unprovoked DVT; (3) patients without history of DVT (the no-DVT controls). Fibrin clot properties, along with thrombin concentration and α2-antiplasmin, were assessed following 3 months of anticoagulation in all DVT patients.Results Compared with the no-DVT controls, the failed thromboprophylaxis group exhibited denser fibrin networks (12.8% lower clot permeability [Ks], p = 0.0008) and impaired fibrinolysis (46.2% longer clot lysis time [CLT], p = 0.0001 and 8% lower rate of D-dimer release from clots, p = 0.0008). In the unprovoked DVT, similar Ks and 14.9% shorter CLT (p = 0.02) were reported compared with the failed thromboprophylaxis group. The failed thromboprophylaxis patients had higher odds of having elevated peak thrombin generation (>241.5 nM, 90th percentile in the no-DVT controls; odds ratio [OR]: 3.62; 95% confidence interval [CI], 1.86–7.06; p = 0.002), and higher odds of having elevated α2-antiplasmin (>115.05%; OR: 3.38; 95% CI, 1.64–6.98; p = 0.001).Conclusion Patients who experienced DVT despite thromboprophylaxis following lower limb trauma display a strongly prothrombotic fibrin clot phenotype, including increased clot density and hypofibrinolysis associated with higher plasma α2-antiplasmin.
Keywords: prothrombotic; fibrin; fibrinolysis; thromboprophylaxis; lower limb trauma